Worship Education in Surah Al-Kautsar Verses 1-3 - Andre Wahyudi; Tria Jainul Mutaqim (Konsultan Jurnal Ilmiah Indonesia, 2026)
Surah Al-Kautsar, although the shortest chapter in the Quran, contains profound theological and pedagogical messages regarding the essence of gratitude and the manifestation of worship. This study aims to analyze the dimensions of worship education contained in Surah Al-Kautsar verses 1-3 and their relevance in shaping Muslim character. The research method used was qualitative, with library research using a thematic interpretation (maudhu'i) approach. Primary data were sourced from the Quranic text and authoritative commentaries, while secondary data were obtained from relevant Islamic education literature. The results show that Surah Al-Kautsar integrates three main pillars of worship education: awareness of God's blessings (tawhid), consistency in ritual worship (salat), and social sacrifice through the act of sacrifice. The prominent educational value is the transformation of gratitude from mere verbal expression into concrete actions that impact individual and social piety. This study concludes that worship education based on Surah Al-Kautsar is highly effective in fostering steadfastness and social awareness amidst the challenges of modern materialism.